Experience -- Based Science and Mathematics Preservice Teacher Education Program. - Brown, William R. (Science Education)
This article focuses on experience-based science and mathematics preservice teacher education program at the Ohio State University. The Teacher Education Program in Science and Mathematics Education at the university is a two-year sequence directed toward the synthesis of theory and practice in preservice teacher education. The sequence consists of five quarters for science majors and four quarters for mathematics majors during their junior or senior years. This article offers an overview of comprehensive majors offered by the Faculty of Science and Mathematics Education. This article presents abstracts of six research studies which have been completed concerning aspects of the program.